Reliability of the Woodway Curve™ Non-Motorized Treadmill for Assessing Anaerobic Performance. - Gonzalez, Adam M.; Wells, Adam J.; Hoffman, Jay R.; Stout, Jeffrey R.; Fragala, Maren S.; Mangine, Gerald T.; McCormack, William P.; Townsend, Jeremy R.; Jajtner, Adam R.; Emerson, Nadia S.; Robinson, Edward H. (Journal of Sports Science & Medicine, 2013)
A curved treadmill offers a practical method of assessing anaerobic power by enabling unrestricted running motion and greater sport specificity. The purpose of this research was to determine reliability of a curved treadmill (cTM) sprint test and to compare performance measures to the traditional Wingate anaerobic power test (WAnT) performed on a cycle ergometer. Thirty-two recreationally active men and women (22.4 ± 2.8 yrs; 1.73 ± 0.08 m; 74.2 ± 13.2 kg) performed four familiarization trials on cTM, followed by two randomly assigned experimental trials consisting of one 30-second maximum effort on either cTM or WAnT. Each trial was separated by at least 48 hours. Repeated measures analysis of variance (ANOVA), interclass correlations (ICC), standard error of measurement (SEM), and minimal differences (MD) were used to determine reliability of familiarization trials on cTM, and Pearson product moment correlations were calculated to compare cTM and WAnT. ANOVA results showed significant differences (p < 0.05) during the four familiarization trials. Post hoc analysis showed significant differences (p < 0.05) between the first two trials. Familiarization trials 3 and 4 showed a high reliability for each performance variable (distance: ICC2,1 = 0.969, %SEM = 2.645, p = 0.157; mean velocity: ICC2,1 = 0.969, %SEM = 2.622, p = 0.173; peak velocity: ICC2,1 = 0.966, %SEM = 3.142, p = 0.033; mean power: ICC2,1 = 0.940, %SEM = 4.140, p = 0.093; and peak power: ICC2,1 = 0.887, %SEM = 11.244, p = 0.669). Participants elicited an average peak power of 1050.4±338.5 Watts on cTM and 1031.4±349.8 Watts on WAnT. Pearson product moment coefficients indicated high correlations between peak power, mean power, and peak velocity (r = 0.75, p < 0.001; r = 0.84, p < 0.001; and r = 0.76, p < 0.001, respectively) derived from cTM and WAnT. In conclusion, results suggest that after two familiarization trials, cTM is a reliable sprint test for recreationally active men and women. In addition, there are strong relationships between cTM and WAnT in assessing anaerobic performance.